A New Model for Elderly Emotional Care Routing and Scheduling With Multi-Agency and the Combination of Nearby Services. Issue 5 (16th March 2023) - Wen, Peihan; Chen, Mo
Abstract: With the intensification of aging, more and more elderly people in China live alone and face the dilemma of less and less communication. However, an intrinsic requirement for the elderly to be accompanied and heard increases the demand for emotional care services. Hence, we focus on emotional care for the elderly and propose the multi-agency bi-objective elderly emotional care routing and scheduling model that considers both the travel and overtime costs of caregivers together with customers' preferences for caregivers. We expand a single agency service mode to a multi-agency joint service mode to avoid a decline in customer satisfaction due to the fact that the single agency cannot meet all customers' requirements in time. In addition, we design a merging method of nearby requirement points to save costs, which permits the same caregiver to provide services to customers in close geographic proximity at the same time on the premise that customers are willing to receive emotional care services with others. We add the constraint that every requirement cannot be rejected, ensuring that all requirements will be responded to. The results show that in the multi-agency joint service mode, all requirements are met without rejection. Compared with the single-agency service model, the proposed model can realize higher customer satisfaction at lower cost, which verified that the proposed multi-agency joint service mode can better meet the needs of a large number of elderly persons' emotional care.